2020
DOI: 10.17220/ijpes.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Measurement and Evaluation Attitude Scale for Physical Education and Sports Teachers

Abstract: The aim of this study is to develop a scale that measures the attitudes of physical education and sports teachers towards measurement and evaluation. In this study, scale development principles and steps of DeVellis (2017) were used. Initially, a literature review was conducted, 19 physical education and sports teachers were interviewed in written form and focus group discussion were held with 7 teachers. Certain statements were converted into a format that can be used in the scale form and an item-pool of 73 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…As a result, it can be said that gender is not effective in the sub-dimension of self-efficacy and deficiencies in online assessment and evaluation. In the literature, the gender variable is defined as the variable that does not make a significant difference in the self-efficacy of both prospective teachers (Oren et al, 2014;Yarali, 2017) and teachers (Baskonus, 2018;Kilic, 2020). However, it was observed that there was a significant difference in favor of male teachers in the sub-dimension of the competencies constituting self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it can be said that gender is not effective in the sub-dimension of self-efficacy and deficiencies in online assessment and evaluation. In the literature, the gender variable is defined as the variable that does not make a significant difference in the self-efficacy of both prospective teachers (Oren et al, 2014;Yarali, 2017) and teachers (Baskonus, 2018;Kilic, 2020). However, it was observed that there was a significant difference in favor of male teachers in the sub-dimension of the competencies constituting self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also studies in the literature showing that there is a negative relationship between teacher experiences and self-efficacy (Guo et al, 2010). In addition, there are studies showing that professional seniority is a factor that affects teachers' self-efficacy regarding measurement and evaluation in education, their level of knowledge and self-efficacy (Bas & Beyhan, 2016;Baskonus, 2018;Kilic, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional trends in education, which are limited to academic knowledge objectives and focus on abstract information as well as absorbing related concepts and rules, are different from contemporary trends which emphasize on practical skills, in addition to knowledge, in order to possess the ability to deal with changing realities of life, and respond to changing labor market requirements [4]. Contemporary trends in teachers education supports a sort of training that stresses on acquiring practical skills, self-confidence and refueling of efficiencies to communicate with others in the labor market [5].…”
Section: Introductionmentioning
confidence: 99%